The prominence of fossil energy resources in ecological sustainability of BRICS: The key role of institutional worth - Zhang, Jie; Ullah, Sami; Khan, Karamat (Frontiers in Environmental Science, 2023)
The relationship between fossil fuel energy resources and environmental degradation has been quantified from theoretical and empirical perspectives. However, none of these studies has considered the conditioning role played by institutions in the nexus, especially for BRICS countries. Therefore, the current study examines the moderating role of institutional quality using annual data from 1996-2018 for BRICS countries. The study employs the novel cross-sectional augmented autoregressive distributed lags (CS-ARDL) estimator, robust to cross-sectional dependency and heterogeneity, for short-run and long-run estimation. Moreover, augmented mean group (AMG) and common correlated effects mean group (CCEMG) estimators are used for robustness analysis. The finding reveals that fossil fuel energy resources, globalization, and growth significantly positively affect the ecological footprint, whereas the institutional quality significantly negatively effects the ecological footprint in BRICS countries. Furthermore, the interaction term of institutional quality with fossil fuel energy resources significantly negatively moderates the fossil fuel energy-EFP nexus. Finally, we performed the Dumitrescu and Hurlin (DH) panel causality analysis to determine the causality direction between the variables. Except for intuitions quality and growth, we found a unidirectional causality for explanatory variables and EFP. The study provides novel empirical evidence and recommends the importance of institutional quality for environmental sustainability.